The characterization of inhibited silicate scale: article - Azman, Ammar Zakwan; Sazali, Rozana Azrina (2019)
Silicate scale has been a significant problem especially in industry such as geothermal, oilfield production and water treatment by which ASP flooding is known as one of enhanced oil recovery method that contribute to this problem. ASP was injected into the reservoir at high pH value and will dissolve the silica in the reservoir. When the high pH of ASP flooding meet with neutral pH connate water, the pH will reduce as well as the solubility of silica hence producing silicate scale as it cannot dissolve anymore. Hence, there are many studies have been conducted to find the most effective ways to inhibit or at least to slow down the formation of silicate scaling. The common method to remove the silicate scale is by traditional mechanical removal. However, this method is not preferred as the scale is already formed and the cost of shutting down the plant for the maintenance is too high and there are other ways to prevent the scale formation. Chemical inhibitors are one of the favored methods to prevent silicate scale formation. There are also several chemical inhibitors being used to slow down the scale formation such as polyphosphino polycarboxylic acid (PPCA), polyvinyl sulfonate (PVS) and polyacrylic acid (PAA). From the previous study, it been reported that magnesium has little effect on these SI and has approximately the same inhibition efficiency